Composite cathode material comprising ceramic oxide electrolyte, lithium electrode material and reinforcing agent
By using composite cathode materials containing LATP, LAGP and NMC in solid-state lithium batteries and sintering at low temperatures, the problem of intimate mechanical contact between the electrode and the electrolyte is solved, and high electrochemical performance and thermal stability are achieved. Improves the circulation performance and safety of lithium-ion batteries.
Patent Information
- Application Number
- CN202380048219.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-06-27
- Publication Date
- 2025-02-18
AI Technical Summary
In solid-state lithium batteries, the mechanical contact between the electrode and the electrolyte is not tight, resulting in high polarization and low utilization of the active material, and side reactions are prone to occur during high-temperature sintering, affecting electrochemical performance.
Composite cathode materials containing lithium titanium aluminum phosphate (LATP) and/or lithium germanium aluminum phosphate (LAGP) ceramic oxide electrolyte materials, lithium nickel-manganese/cobalt oxide (NMC) cathode materials and lithium halide are used and at low temperatures Sintering is carried out to enhance electrochemical properties and thermal stability through lithium halide.
The high electrochemical performance and thermal stability of the composite cathode material sintered at low temperatures is achieved, which reduces the occurrence of side reactions and improves the circulation performance and safety of lithium-ion batteries.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
[0001] Technical Field and Background Art
[0002] The present invention relates to a solid composite cathode material comprising a ceramic oxide electrolyte material and a lithium electrode material. The present invention also relates to a method for preparing the solid material, an electrochemical cell such as a solid-state battery comprising the solid material, and the use of the solid material in an electrochemical cell such as a solid-state battery, in particular as a composite cathode material.
[0003] The three main functional components of a lithium-ion battery are the anode, cathode, and electrolyte. Although there are many variations, the anode of a conventional lithium-ion battery is usually made of carbon or metallic lithium, the cathode is usually made of a transition metal oxide (particularly oxides of cobalt, nickel, and / or manganese), and the electrolyte is usually a non-aqueous solvent containing a lithium salt. For example, a mixture of an organic carbonate and lithium hexafluorophosphate is a well-known liquid electrolyte for lithium-ion batteries.
[0004] A significant disadvantage of liquid electrolytes is that the constituent components, especially the solvents, are flammable, which poses a significant safety risk during normal operation and especially in the event of an accident. Another disadvantage is inherent to the liquid nature of the electrolyte, which is associated with an increased risk of leakage and of environmental contamination in the event of a spill or leak.
[0005] Recently, efforts have been made to develop solid electrolytes that allow solid-state lithium-ion batteries to be provided. Such solid-state batteries have significantly reduced EHS (environmental, health and safety) hazards. Solid electrolytes can be used as electrolytes as well as separators, physically separating the anode material and the cathode material to prevent short circuits.
[0006] In the absence of liquid fluidity, it is challenging to obtain intimate contact between solid electrolytes and electrodes. Periodic electrode expansion and contraction during cycling further deteriorates the mechanical contact between particles. Therefore, high polarization and low utilization of active materials are common in solid-state lithium batteries. Therefore, an important key to achieving solid-state lithium batteries with competitive performance relies on the construction of a stable and tight interface between electrodes and electrolytes. Direct co-sintering of electrodes and electrolytes is used as a simple method to obtain good interfacial contact. However, the necessary high temperature treatment (>600°C) promotes ionic interdiffusion across the interface, resulting in side reactions between electrodes and solid electrolytes, which, depending on the material being sintered, may be detrimental to the electrochemical performance. It has been proposed in the art to alleviate this problem by coating the cathode material with a buffer layer such as Nb, LiNbO2, BaTiO3 before sintering.
[0007] US2021 / 0083249A1 discloses coating LLZO particles with a lithium carbonate layer to which 2 wt.% lithium fluoride is added, followed by sintering at 900°C or higher.
[0008] One object of the present invention is to provide an improved composite cathode material, in particular a composite cathode material having improved electrochemical properties such as improved cycling performance. Another object of the present invention is to provide a composite cathode material that can be sintered at low temperatures. Summary of the invention
[0009] The inventors have found that one or more of the objects of the present invention can be achieved by providing a composite cathode material comprising lithium aluminum titanium phosphate (LATP) and / or lithium aluminum germanium phosphate (LAGP) electrolyte material, lithium nickel-manganese / cobalt oxide (e.g., NMC) cathode material, and lithium halide. As will be shown in the accompanying examples, it is found that the addition of lithium halide to the selected electrolyte and cathode material strongly enhances electrochemical performance (particularly cycling performance) even without sintering the composite cathode material. It is also found that the addition of lithium halide to the selected electrolyte and cathode material allows these materials to be co-sintered at extremely low temperatures, surprisingly producing a sintered composite cathode material with limited degradation of LATP / LAGP or cathode material. In other words, the thermal stability of the composite cathode material is increased, so that the sintering temperature is reached without decomposing the composite cathode material. It is also found that even after sintering, there is an enhanced electrochemical performance provided by the addition of lithium halide. As shown herein, it is found that the addition of lithium halide in the context of the present invention improves the thermal stability of the composite cathode.
[0010] Thus, in a first aspect of the present invention, there is provided a solid composite cathode composition comprising:
[0011] Ceramic oxide electrolyte materials containing lithium aluminum titanium phosphate (LATP) and / or lithium aluminum germanium phosphate (LAGP);
[0012] An electrode active material comprising Li, M and O, wherein M comprises Ni and one or both of Mn and Co; and
[0013] ● Enhancer, the enhancer is LiX, wherein X is a halogen ion.
[0014] In another aspect of the present invention, there is provided a method for preparing a composite cathode, the method comprising the steps of:
[0015] a) providing at least the following precursors:
[0016] Ceramic oxide electrolyte materials containing lithium aluminum titanium phosphate (LATP) and / or lithium aluminum germanium phosphate (LAGP);
[0017] An electrode active material comprising Li, M and O, wherein M comprises one or both of Mn and Co and Ni;
[0018] ● a reinforcing agent, the reinforcing agent being LiX, wherein X is a halide ion; and
[0019] ●Optionally, a carbon-based conductive additive;
[0020] b) preparing a substantially homogeneous mixture comprising the precursor provided in step (a); and
[0021] c) Optionally, sintering the mixture of step (b).
[0022] In another aspect of the invention, there is provided an electrode comprising a solid composite cathode material as described herein in combination with a binder, such as a polymeric binder.
[0023] In another aspect of the present invention, there is provided an electrochemical cell comprising a solid composite cathode material as described herein.
[0024] In another aspect of the invention there is provided the use of a solid composite cathode material as described herein as a cathode of an electrochemical cell.
[0025] In another aspect of the invention, there is provided a battery, more particularly a lithium ion battery or a lithium metal battery, comprising at least one electrochemical cell comprising a solid composite cathode material as described herein, such as two or more electrochemical cells according to the invention.
[0026] In another aspect of the present invention, a method is provided for manufacturing or operating an automobile, a computer, a personal digital assistant, a mobile phone, a watch, a camcorder, a digital camera, a thermometer, a calculator, a laptop BIOS, a communication device, a remote car lock, and a stationary application (such as an energy storage device for a power plant) by using at least one battery or at least one electrochemical cell comprising a solid composite cathode material as described herein.
[0027] In another aspect of the present invention, there is provided a use of an electrochemical cell comprising the solid composite cathode material of the present invention in a motor vehicle, a bicycle operated by an electric motor, a robot, an aircraft (e.g. an unmanned aerial vehicle including a drone), a ship, a satellite or a stationary energy storage device.
[0028] In another aspect of the present invention, there is provided a use of a lithium halide for improving the electrochemical properties (e.g., cycling performance) of an electrochemical cell comprising a composite cathode material, wherein the composite cathode material comprises lithium aluminum titanium phosphate (LATP) and / or lithium aluminum germanium phosphate (LAGP) electrolyte material and a lithium nickel-manganese-cobalt oxide (NMC) cathode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The temperature-dependent degradation of the NMC-LATP mixture is shown, as evidenced by the XRD spectra of Comparative Examples 1, 2, and 4.
[0030] Figure 2 The temperature-dependent degradation of the cycle performance of the NMC-LATP mixtures of Comparative Examples 1-3 is shown.
[0031] Figure 3 It shows the enhancement effect of adding lithium fluoride on the electrochemical performance of the composite cathode materials of Examples 5-7 compared with Comparative Example 1.
[0032] Figure 4 It shows the enhancement effect of adding lithium fluoride on the electrochemical performance of the composite cathode materials of Examples 8-10 compared with Comparative Example 2. DETAILED DESCRIPTION
[0033] In the following specific embodiments, preferred embodiments are described in detail to practice the present invention. Although the present invention is described with reference to these specific preferred embodiments, it should be understood that the present invention is not limited to these preferred embodiments. On the contrary, the present invention includes many substitutions, modifications and equivalent forms, which will become apparent by considering the following specific embodiments.
[0034] The expressions "composite cathode material" and "composite cathode composition" are used interchangeably throughout this document.
[0035] The expression "sintering" as used in this application refers to the process of treating a solid material by heat treatment and / or pressure without melting it to the liquidus point.
[0036] In a first aspect of the present invention, there is provided a solid composite cathode composition comprising:
[0037] Ceramic oxide electrolyte materials containing lithium aluminum titanium phosphate (LATP) and / or lithium aluminum germanium phosphate (LAGP);
[0038] An electrode active material comprising Li, M and O, wherein M comprises Ni and one or both of Mn and Co; and
[0039] ● Enhancer, the enhancer is LiX, wherein X is a halogen ion.
[0040] Preferably, the solid composition of the present invention is a substantially homogeneous mixture. In a particular embodiment of the present invention, the solid composition is a substantially homogeneous mixture that comprises discrete particles of an optionally sintered ceramic oxide electrolyte material, an electrode active material, and a lithium halide. Such a solid comprising discrete particles of an optionally sintered ceramic oxide electrolyte material, an electrode active material, and a lithium halide can be obtained by simply dry-mixing the solid particles of the ceramic oxide electrolyte material, the electrode active material, and the lithium halide and then optionally sintering the mixture. Those skilled in the art will understand that although sintering will result in a tight solid-solid interface or even the fusion of ceramic grains, the resulting solid is still substantially different from a solid in which one compound is coated on another compound. In some embodiments of the present invention, at least the reinforcing agent is substantially uniformly distributed throughout the composition.
[0041] Preferably, the lithium aluminum germanium phosphate (LAGP) referred to herein has the formula Li 1+n Al n Ge n (PO4) n where 0 < n < 1, preferably where 0.2 < n < 0.8, more preferably where 0.3 < n < 0.5. According to the present invention, n referred to herein is measured by scanning electron microscopy-energy dispersive X-ray (SEM-EDX) analysis.
[0042] Preferably, the lithium aluminum titanium phosphate (LATP) referred to herein has the formula Li 1+m Al m Ti 2-m (PO4)3, where 0 < m < 1, preferably where 0.2 < m < 0.8, more preferably where 0.3 < m < 0.5. According to the present invention, m referred to herein is measured by scanning electron microscopy-energy dispersive X-ray (SEM-EDX) analysis.
[0043] Preferably, the ceramic oxide electrolyte material comprises lithium aluminum titanium phosphate (LATP), more preferably LATP of the formula Li 1+ m Al m Ti 2-m (PO4)3, where 0 < m < 1, preferably where 0.2 < m < 0.8, more preferably where 0.3 < m < 0.5. According to the present invention, m referred to herein is measured by scanning electron microscopy-energy dispersive X-ray (SEM-EDX) analysis.
[0044] Preferably, the ceramic oxide electrolyte material consists of an optionally doped LATP and / or LAGP as described herein, most preferably, consists of an optionally doped LATP. In some embodiments, the LATP and / or LAGP has been optionally doped with a dopant selected from tantalum, niobium, aluminum, indium, tin, antimony, bismuth, yttrium, germanium, calcium, strontium, barium, hafnium, or a combination thereof. If doped, the dopant is typically present in an amount of less than 2 wt.% (based on the total weight of the LATP and / or LAGP), preferably less than 1 wt.% (based on the total weight of the LATP and / or LAGP). In embodiments in which the ceramic oxide electrolyte material consists of an optionally doped LATP and / or LAGP as described herein, it is preferred that the solid composite cathode composition does not contain other oxide materials other than the electrode active material.
[0045] As will be appreciated by those skilled in the art, the electrode active materials comprising Li, M and O discussed herein are cathode active materials, which are also referred to as positive electrode active materials. Depending on the mode of operation of the electrochemical cell comprising the electrode active material, the cathode polarity may be positive or negative. Preferably, the electrode active material comprises Li, M and O, wherein M comprises:
[0046] - Ni with a content of x, wherein relative to M, 55.0mol%≤x≤95.0mol%;
[0047] - Mn with a content of y, wherein 0.0 mol%≤y≤40.0 mol% relative to M;
[0048] - Co with a content of z, wherein relative to M, 0.0mol%≤z≤40.0mol%;
[0049] - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0050] - wherein x+y+z+a is 100.0 mol%;
[0051] Preferably, wherein M comprises:
[0052] - Ni with a content of x, wherein relative to M, 55.0 mol%≤x≤80.0 mol%;
[0053] - Mn with a content of y, wherein relative to M, 10.0 mol%≤y≤30.0 mol%;
[0054] - Co with a content of z, wherein relative to M, 10.0mol%≤z≤30.0mol%;
[0055] - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0056] - wherein x+y+z+a is 100.0 mol%;
[0057] More preferably,
[0058] Where M contains:
[0059] - Ni with a content of x, wherein 55.0 mol%≤x≤70.0 mol% relative to M;
[0060] - Mn with a content of y, wherein relative to M, 15.0mol%≤y≤25.0mol%;
[0061] - Co with a content of z, wherein relative to M, 15.0mol%≤z≤25.0mol%;
[0062] - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0063] - wherein x+y+z+a is 100.0 mol%.
[0064] In some particularly preferred embodiments, x is about 60 mol %, y is about 20 mol %, and z is about 20 mol %.
[0065] In some particularly preferred embodiments, a=0.0 mol %.
[0066] According to the present invention, x, y, z and a referred to herein are measured by inductively coupled plasma-optical emission spectroscopy (ICP-OES).
[0067] In particularly preferred embodiments, the electrode active material described herein is the only electrode active material contained in the composite cathode material of the present invention.
[0068] It is particularly preferred that the reinforcing agent comprises lithium fluoride (LiF). As shown in the accompanying examples, excellent electrochemical results have been obtained using selected electrolyte materials and electrode active materials in combination with LiF before and after sintering. In a preferred embodiment of the present invention, the reinforcing agent is LiX, wherein X is a halide ion and wherein at least 50 mol% or more of X represents F, preferably, at least 80 mol% of X represents F, and most preferably, X represents F (so that the reinforcing agent consists of lithium fluoride (LiF)).
[0069] Typically, the reinforcing agent is present in an amount of at least 0.5 wt.% (based on the total weight of the composition). For example, the reinforcing agent can be present in an amount of at least 0.8 wt.% (based on the total weight of the composition), at least 1.2 wt.% (based on the total weight of the composition), or at least 1.5 wt.% (based on the total weight of the composition). As shown in the attached examples, even at these low concentrations, the reinforcing agent has significantly enhanced the electrochemical properties before and after sintering. The inventors have found that when used at a high ratio, the reinforcing agent surprisingly shows a significant further increase in the beneficial effect. Therefore, according to a preferred embodiment of the present invention, the reinforcing agent is present in an amount of at least 4 wt.% (based on the total weight of the composition), preferably at least 4.5 wt.% (based on the total weight of the composition). According to a highly preferred embodiment of the present invention, the reinforcing agent is present in an amount of at least 7 wt.%, more preferably at least 8 wt.% (based on the total weight of the composition). Preferably, the enhancer is present in an amount less than 25 wt.% (based on the total weight of the composition), preferably less than 20 wt.% (based on the total weight of the composition), most preferably less than 14 wt.% (based on the total weight of the composition).
[0070] In a preferred embodiment of the present invention, the ratio (w / w) of electrode active material to ceramic oxide electrolyte material is at least 1: 1, preferably at least 1.5: 1, more preferably at least 1.8: 1, most preferably at least 2: 1. Preferably, the ratio is less than 8: 1, preferably less than 6: 1, more preferably less than 3: 1, most preferably less than 2.5: 1.
[0071] An optional but highly preferred additional component of the composite cathode material of the present invention is a conductive aid, particularly a carbon-based conductive aid. The inventors have found that when sintering a composite cathode composition containing a carbon-based conductive aid, such carbon-based conductive aids exhibit significant oxidation (and associated functional loss). Formulations comprising reinforcing agents according to the present invention overcome such problems because they allow sintering at low temperatures, thereby limiting the reactivity between components, including carbon oxidation. The carbon-based conductive aid can be any carbon-rich material, such as any material containing at least 95wt.% carbon, preferably any material containing at least 99wt.% carbon. Examples of suitable materials are graphite, carbon black, carbon fiber, carbon nanotubes, graphene, and combinations thereof. When used in the solid composite cathode composition of the present invention, the inventors have found that a highly preferred carbon-based conductive aid that exhibits improved electrochemical performance compared to other carbon-based conductive aids is carbon black. Carbon black is known to those skilled in the art and includes variants such as acetylene black or super C65.
[0072] In a preferred embodiment, the carbon-based conductive aid as described herein is present in the solid composite cathode composition of the present invention in an amount of at least 0.5 wt.% (based on the combined weight of the ceramic oxide electrolyte material and the electrode active material), preferably at least 1 wt.% (based on the combined weight of the ceramic oxide electrolyte material and the electrode active material), and more preferably at least 3 wt.% (based on the combined weight of the ceramic oxide electrolyte material and the electrode active material). Typically, the carbon-based conductive aid is present in an amount of less than 12 wt.% (based on the combined weight of the ceramic oxide electrolyte material and the electrode active material), preferably less than 9 wt.% (based on the combined weight of the ceramic oxide electrolyte material and the electrode active material), and more preferably less than 7 wt.% (based on the combined weight of the ceramic oxide electrolyte material and the electrode active material).
[0073] Generally, it is preferred that the combined amount of ceramic oxide electrolyte material, electrode active material, reinforcing agent, and optional carbon-based conductive aid is at least 90 wt.% (based on the total weight of the composition), preferably at least 95 wt.% (based on the total weight of the composition), and more preferably at least 98 wt.% (based on the total weight of the composition). In some embodiments, the solid composite cathode composition consists essentially of ceramic oxide electrolyte material, electrode active material, reinforcing agent, and optional carbon-based conductive aid.
[0074] In a highly preferred embodiment of the invention, the solid composite cathode composition has been sintered. In a particularly preferred embodiment, the material has been sintered at a temperature below 600°C, preferably below 500°C, more preferably below 450°C. In a particularly preferred embodiment, the material has been sintered at a temperature above 200°C, preferably above 300°C, more preferably above 350°C. In a particularly preferred embodiment, the material has been sintered at a temperature in the range of 200°C to 600°C, preferably in the range of 300°C to 500°C, more preferably in the range of 350°C to 450°C. Preferably, the total time for which the material is subjected to a temperature above 200°C is in the range of 5 minutes to 48 hours, preferably in the range of 10 minutes to 24 hours, more preferably in the range of 30 minutes to 10 hours. Sintering is optionally performed while subjecting the material to an elevated pressure, for example a pressure of at least 0.1 GPa or at least 0.5 GPa. In some embodiments, sintering is performed while subjecting the material to an elevated pressure in the range of 1 GPa to 5 GPa, preferably 1 GPa to 3 GPa, to achieve high compaction while avoiding grain splitting. In any of the embodiments described herein, it is preferred that the solid composite cathode composition has been sintered under an inert atmosphere or air, preferably air. Without wishing to be bound by any theory, given the degradation of the material at elevated sintering temperatures, the inventors believe that the temperature and duration at which the composition is subjected to sintering can be derived from the final product by constructing a temperature-time calibration curve at different temperatures, and sampling different time points of each curve to determine the relevant X-ray diffraction spectra of the material at different temperatures and durations, and comparing the X-ray diffraction spectrum of the material to be analyzed with the recorded X-ray diffraction spectrum for the calibration curve.
[0075] Preferably, the solid composite cathode compositions provided herein have a ratio A of less than 2.3.
[0076] in
[0077] A = (DC C / 20 ) / (DC 1C )
[0078] where the ratio A is determined on a button cell by performing five consecutive full discharge cycles at each C-rate of C / 20, C / 10, C / 5, C / 2 and 1C in that order,
[0079] And DC C / 20 is the first discharge capacity in mAh / g determined at a C-rate of C / 20,
[0080] And DC 1Cis the first discharge capacity in mAh / g determined at a C-rate of 1 C. Preferably, Ratio A is in the range of 1.5 to 2.5, more preferably in the range of 1.5 to 2.2, most preferably in the range of 1.5 to 1.9. Preferably, Ratio A is determined immediately after assembly (without aging), preferably at 2.7 V to 4.3 V, preferably at 2.9 V to 3.1 V, for example using a TOYO battery cycler, on a button cell. Preferably, the ratio A is determined on a button cell prepared by mixing the solid cathode composition with polyvinylidene fluoride (PVDF) in a ratio of 90:10 to obtain a solution of 1.4 mL to 1.6 mL of N-methyl-2-pyrrolidone solvent (NMP) solvent with a total weight of 400 mg; casting the resulting slurry on an aluminum foil with a wet thickness of 300 µm using a doctor blade, and drying the laminate at 80° C. in a dynamic vacuum overnight, and then punching the dried laminate into a disk having a diameter selected in such a way that the area capacity (mAh / cm 2 ) is maintained at 0.3 mAh / cm 2 Up to 0.45 mAh / cm 2 range, where the composite cathode material loading corresponds to 2 mg / cm 2 Up to 3mg / cm 2 ; and the disks were densified with a uniaxial pressure of 0.1 MPa to 0.3 MPa and dried at 120°C overnight, and then the battery was assembled with a lithium metal anode and 1 M LiPF6 in EC-DMC (ethylene carbonate: dimethyl carbonate 3:7) as the electrolyte.
[0081] In another aspect of the present invention, there is provided a method for preparing a composite cathode composition, preferably a composition as hereinbefore described, comprising the steps of:
[0082] a) providing at least the following precursors:
[0083] Ceramic oxide materials comprising lithium aluminum titanium phosphate (LATP) and / or lithium aluminum germanium phosphate (LAGP);
[0084] An electrode active material comprising Li, M and O, wherein M comprises one or both of Mn and Co and Ni;
[0085] ● a reinforcing agent, the reinforcing agent being LiX, wherein X is a halide ion; and
[0086] ●Optionally, a carbon-based conductive additive;
[0087] b) preparing a substantially homogeneous mixture comprising the precursor provided in step (a); and
[0088] c) Optionally, sintering the mixture of step (b).
[0089] The preferred embodiments of the composite cathode composition, in particular the identity and (relative) amounts of ceramic oxide material, electrode active material, reinforcing agent and carbon-based conductivity aid as explained herein in the context of the composite cathode composition, apply equally to the method for preparing the composite cathode composition described herein.
[0090] Preferably, step (b) is a dry mixing step and can be performed using any suitable means known to those skilled in the art, such as a simple pestle and mortar, a ribbon mixer, a tumbler, a plowshare mixer, a paddle mixer, a conical screw mixer, etc. Step (b) may also include size reduction or comminution of one or more of the precursors provided in step (a), such as using a ball mill, a hammer mill, a pin mill, etc.
[0091] Step (b) may comprise a first step of mixing a subset of the precursors provided in step (a) followed by the addition of the remaining precursors provided in step (a).
[0092] Preferably, step (c) comprises sintering at a temperature below 600°C, preferably below 500°C, more preferably below 450°C. In a particularly preferred embodiment, the material has been sintered at a temperature above 200°C, preferably above 300°C, more preferably above 350°C. In a particularly preferred embodiment, the material has been sintered at a temperature in the range of 200°C to 600°C, preferably in the range of 300°C to 500°C, more preferably in the range of 350°C to 450°C. Preferably, the total time for which the material is subjected to a temperature above 200°C is in the range of 5 minutes to 48 hours, preferably in the range of 10 minutes to 24 hours, more preferably in the range of 30 minutes to 10 hours. Sintering is optionally performed while subjecting the material to elevated pressure, for example a pressure of at least 0.1 GPa or at least 0.5 GPa. In some embodiments, sintering is performed while subjecting the material to elevated pressure in the range of 1 GPa to 3 GPa, preferably 1 GPa to 5 GPa, to ensure adequate compaction while avoiding grain splitting.
[0093] In another aspect of the present invention, an electrode comprising a solid composite cathode material of the present invention is provided. In a particularly preferred embodiment of the present invention, the electrode comprises a solid composite cathode material of the present invention in combination with a binder such as a polymer binder. The binder is not particularly limited, and the binder can be any suitable polymer binder, such as polyimide (PI), polyvinylidene chloride (PVdC), polyethylene oxide (PEO), polyvinylidene fluoride (PVdF), etc.
[0094] In another aspect of the present invention, there is provided an electrochemical cell comprising a solid composite cathode material as described herein.
[0095] In another aspect of the invention there is provided the use of a solid composite cathode material as described herein as a cathode of an electrochemical cell.
[0096] In another aspect of the invention, there is provided a battery, more particularly a lithium ion battery or a lithium metal battery, comprising at least one electrochemical cell comprising a solid composite cathode material as described herein, such as two or more electrochemical cells according to the invention.
[0097] In another aspect of the present invention, a method is provided for manufacturing or operating an automobile, a computer, a personal digital assistant, a mobile phone, a watch, a camcorder, a digital camera, a thermometer, a calculator, a laptop BIOS, a communication device, a remote car lock, and a stationary application (such as an energy storage device for a power plant) by using at least one battery or at least one electrochemical cell comprising a solid composite cathode material as described herein.
[0098] In another aspect of the present invention, there is provided a use of an electrochemical cell comprising the solid composite cathode material of the present invention in a motor vehicle, a bicycle operated by an electric motor, a robot, an aircraft (e.g. an unmanned aerial vehicle including a drone), a ship, a satellite or a stationary energy storage device.
[0099] In another aspect of the present invention, there is provided a use of a lithium halide for improving the electrochemical properties (e.g., cycling performance) of an electrochemical cell comprising a composite cathode material, the composite cathode material comprising: a ceramic oxide electrolyte material comprising lithium aluminum titanium phosphate (LATP) and / or lithium aluminum germanium phosphate (LAGP); an electrode active material comprising Li, M and O, wherein M comprises one or both of Mn and Co and Ni; and optionally, a carbon-based conductive aid. Preferred embodiments of the composite cathode composition, in particular the identity and (relative) amounts of the ceramic oxide material, electrode active material, enhancer and carbon-based conductive aid as explained herein in the context of the composite cathode composition, also apply to the use of the lithium halide described herein.
[0100] Example
[0101] I. Preparation of composite cathode materials
[0102] The composite cathode material according to the invention was prepared in 2 g batches using the following starting products in the following order: NMC (LiNi 0.6 Mn 0.2 Co 0.2O2), LiF (99.98% (metallic substrate)), carbon black (acetylene black - KetjenBlack ® ) and LATP (Li 1+m Al m Ti 2-m (PO4)3, where 0.3 < m < 0.5, according to SEM - EDX). In a glove box (O2 < 1 ppm and H2O < 1 ppm), appropriate amounts of starting materials were weighed and mixed using an agate mortar and pestle. The composite materials were heat - treated in a GAF (muffle furnace) under a controlled atmosphere, which had been pre - calibrated under similar heating conditions. The samples were heated at a rate of 1 °C / min, then held at the sintering temperature (without high pressure) for 1 hour, and cooled back to room temperature. All samples were heated in 30 mL alumina (Al2O3) crucibles with open lids. The transfer time of the samples between the glove box and the furnace was controlled to avoid exposure to ambient conditions. Additionally, after heat - treatment, the samples were transferred to the glove box at a temperature range of 120 °C to 150 °C to avoid moisture absorption.
[0103] Control materials were prepared in the same way, but without LiF.
[0104] NMC, LATP, and carbon black were always used at a ratio of 65:30:05 (w / w) respectively. LiF was added in amounts of 0 wt.%, 2 wt.%, 5 wt.%, and 10 wt.% (based on the combined weight of NMC, LATP, and carbon black). In other words, LiF was added at ratios of (LiF):(NMC + LATP + carbon black) of 0:100, 2:100, 5:100, and 10:100 (w / w) respectively, as shown in the table below. As - received NMC (unsintered, pure) was also used as a reference for X - ray diffraction spectra.
[0105]
[0106] II. Preparation of electrodes
[0107] Slurries of the comparative examples 1 - 4 and the examples 5 - 10 of the composite cathode materials in an amount of 400 mg were prepared with polyvinylidene fluoride (PVDF) at a ratio of 90:10 in 1.4 - 1.6 ml of N - methyl - 2 - pyrrolidone solvent (NMP). PVDF was dissolved in the NMP solvent using a magnetic stirrer for 2 hours, after which the composite cathode material was added and stirring continued overnight. The slurry was cast onto an aluminum foil with a wet thickness of 300 µm using a doctor blade. The laminate was dried overnight at 80 °C under dynamic vacuum. The dried laminate was punched into discs and the diameter was selected in such a way that the areal capacity (mAh / cm 2 ) was maintained at 0.3 mAh / cm2 Up to 0.45 mAh / cm 2 range, where the cathode active material loading corresponds to 2 mg / cm 2 Up to 3mg / cm 2 The disks were densified with a uniaxial pressure of 0.1 MPa to 0.3 MPa and dried overnight at 120 °C before assembling the cells. All processes were performed in a dry room (dew point of approximately 37 °C).
[0108] III. Determination of electrochemical performance
[0109] 2032 coin cells were assembled using the composite cathode disks prepared as described in the previous section, a lithium metal anode, and a 1M LiPF6 solution in EC-DMC (ethylene carbonate: dimethyl carbonate 3:7) as the electrolyte. Immediately after cell assembly (without aging), the coin cells were subjected to constant current charge-discharge between 2.7-4.3 V, and the cycling performance was tested using a TOYO battery cycler.
[0110] The cycling scheme consisted of 5 cycles at C rates of C / 20, C / 10, C / 5, C / 2, 1C followed by 100 cycles at C / 10. The capacity values were normalized to the weight of the active material (NMC) and the results were verified for reproducibility. Glass fiber was used as separator.
[0111] IV. Determination of X-ray diffraction spectra
[0112] XRD measurements were performed with a BRUKER D8 Endeavor X-ray diffractometer equipped with a LYNXEYE XE-T detector using Co radiation (λ: Kα1 = 1.78897Å, Kα2 = 1.79285Å). The samples were measured in the 2θ range of 10°-130° with a step size of 0.016° and a total time of 19.20 s / step. In order to avoid the amorphous background from a common support due to the limited amount of sample, a silicon support was used. The comparison of the peaks was obtained after background subtraction and Kα2 stripping (to avoid double peaks generated by a non-monochromatic source). Considering that the peaks used for comparison are (101), (012), (006) and (104) from NMC, a crystalline structural transition is observed around these peaks. The intensity is normalized to the (104) peak of NMC at 2θ = 52°.
[0113] V. Results
[0114] Figure 1The temperature-dependent degradation of the NMC-LATP blend is shown, as evidenced by the XRD spectra of Comparative Examples 2 and 4. It can be observed that the composite cathode material of Comparative Example 4 (treated at 500°C) shows significant degradation.
[0115] Figure 2 The temperature-dependent degradation of the cycling performance of the NMC-LATP mixtures of Comparative Examples 1 to 3 is shown. It can be observed that the composite cathode material of Comparative Example 2 (treated at 400°C) already has significantly reduced performance, while the composite cathode material of Comparative Example 3 (treated at 470°C) no longer functions.
[0116] Figure 3 It shows the enhancing effect of adding lithium fluoride on the electrochemical performance of the composite cathode materials of Examples 5-7 compared to Comparative Example 1. The electrochemical performance is enhanced even before sintering, and is particularly improved at high C-rates.
[0117] Figure 4 It shows the enhancing effect of adding lithium fluoride on the electrochemical performance of the composite cathode materials of Examples 8-10 compared to Comparative Example 2. The electrochemical performance is particularly enhanced at high C-rates and high LiF loadings.
Claims
1. A solid composite cathode composition, comprising: Ceramic oxide electrolyte materials containing lithium aluminum titanium phosphate (LATP) and / or lithium aluminum germanium phosphate (LAGP); An electrode active material comprising Li, M and O, wherein M comprises Ni and one or both of Mn and Co; and - A reinforcing agent, wherein the reinforcing agent is LiX, wherein X is a halogen ion.
2. The composition according to claim 1, wherein the ceramic oxide electrolyte material comprises LATP of the formula Li 1+m Al m Ti 2-m (PO4)3, where 0 < m < 1, preferably, where 0.2 < m < 0.8, more preferably, where 0.3 < m < 0.
5.
3. The composition according to claim 1 or 2, wherein the electrode active material comprises Li, M and O, wherein M comprises: - Ni with a content of x, wherein relative to M, 55.0mol%≤x≤95.0mol%; - Mn with a content of y, wherein 0.0 mol%≤y≤40.0 mol% relative to M; - Co with a content of z, wherein relative to M, 0.0mol%≤z≤40.0mol%; - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O; - wherein x+y+z+a is 100.0 mol%; Preferably, wherein M comprises: - Ni with a content of x, wherein relative to M, 55.0 mol%≤x≤80.0 mol%; - Mn with a content of y, wherein relative to M, 10.0 mol%≤y≤30.0 mol%; - Co with a content of z, wherein relative to M, 10.0mol%≤z≤30.0mol%; - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O; - wherein x+y+z+a is 100.0 mol%.
4. A composition according to any one of the preceding claims, wherein the enhancer is lithium fluoride.
5. The composition according to any one of the preceding claims, wherein the enhancer is present in an amount of at least 0.5 wt.% (based on the total weight of the composition), preferably at least 4 wt.% (based on the total weight of the composition), more preferably at least 8 wt.% (based on the total weight of the composition).
6. A composition according to any one of the preceding claims, wherein the ratio (w / w) of the electrode active material to the ceramic oxide electrolyte material is at least 1 :1, preferably at least 1.5:1, more preferably at least 1.8:
1.
7. A composition according to any one of the preceding claims, wherein the solid further comprises a carbon-based conductivity aid.
8. The composition according to claim 7, wherein the carbon-based conductive aid is selected from graphite, carbon black, carbon fiber, carbon nanotube, graphene, and combinations thereof, preferably, the carbon-based conductive aid is selected from carbon black.
9. The composition according to claim 7 or 8, comprising at least 0.5 wt.% (based on the combined weight of the ceramic oxide electrolyte material and the electrode active material), preferably at least 1 wt.% (based on the combined weight of the ceramic oxide electrolyte material and the electrode active material), more preferably at least 3 wt.% (based on the combined weight of the ceramic oxide electrolyte material and the electrode active material) of a carbon-based conductive additive.
10. A composition according to any one of the preceding claims, wherein the combined amount of the ceramic oxide electrolyte material, the electrode active material, the reinforcing agent and the optional carbon-based conductivity aid is at least 90 wt.% (based on the total weight of the composition), preferably at least 95 wt.% (based on the total weight of the composition).
11. A composition according to any one of the preceding claims, wherein the enhancer is substantially uniformly distributed throughout the composition.
12. The composition according to any one of the preceding claims, which has been sintered, preferably, the composition has been sintered at a temperature below 600°C, more preferably, the composition has been sintered at a temperature below 500°C.
13. A method for preparing a composite cathode composition, preferably a composition according to any one of claims 1 to 12, comprising the steps of: a) providing at least the following precursors: Ceramic oxide materials comprising lithium aluminum titanium phosphate (LATP) and / or lithium aluminum germanium phosphate (LAGP); An electrode active material comprising Li, M and O, wherein M comprises one or both of Mn and Co and Ni; ● a reinforcing agent, wherein the reinforcing agent is LiX, wherein X is a halogen ion; as well as ●Optionally, a carbon-based conductive additive; b) preparing a substantially homogeneous mixture comprising the precursor provided in step (a); and c) Optionally, sintering the mixture of step (b).
14. The method according to claim 13, wherein: Step (c) is performed, and wherein, • the temperature during sintering of step (c) is below 500°C, preferably below 450°C; and • Preferably, the pressure during sintering is in the range of 1 GPa to 3 GPa.
15. An electrochemical cell comprising the solid material according to any one of claims 1 to 12.
Citation Information
Patent Citations
Additive to ceramic ion conducting material to mitigate the resistive effect of surface carbonates and hydroxides
US20210083249A1